Comparative Genomic Analysis of a New Tellurite-Resistant Psychrobacter Strain Isolated from the Antarctic Peninsula - Vasquez-Guzman, C; Arenas-Salinas, F; Muñoz-Villagran, C; Morales-Sierra, E; Cornejo-Leiva, F; Figueroa, M (PeerJ Inc., 2018)
The Psychrobacter genus is a cosmopolitan and diverse group of aerobic, cold-adapted, Gram-negative bacteria exhibiting biotechnological potential for low-temperature applications including bioremediation. Here, we present the draft genome sequence of a bacterium from the Psychrobacter genus isolated from a sediment sample from King George Island, Antarctica (3,490,622 bp; 18 scaffolds; G + C = 42.76%). Using phylogenetic analysis, biochemical properties and scanning electron microscopy the bacterium was identified as Psychrobacter glacincola BNF20, making it the first genome sequence reported for this species. P. glacincola BNF20 showed high tellurite (MIC 2.3 mM) and chromate (MIC 6.0 mM) resistance, respectively. Genome-wide nucleotide identity comparisons revealed that P. glacincola BNF20 is highly similar (> 90%) to other uncharacterized Psychrobacter spp. such as JCM18903, JCM18902, and P11F6. Bayesian multi-locus phylogenetic analysis showed that P. glacincola BNF20 belongs to a polyphyletic clade with other bacteria isolated from polar regions. A high number of genes related to metal(loid) resistance were found, including tellurite resistance genetic determinants located in two contigs: Contig LIQB01000002.1 exhibited five ter genes, each showing putative promoter sequences (terACDEZ), whereas contig LIQB1000003.2 showed a variant of the terZ gene. Finally, investigating the presence and taxonomic distribution of ter genes in the NCBI s RefSeq bacterial database (5,398 genomes, as January 2017), revealed that 2,623 (48.59%) genomes showed at least one ter gene. At the family level, most (68.7%) genomes harbored one ter gene and 15.6% exhibited five (including P. glacincola BNF20). Overall, our results highlight the diverse nature (genetic and geographic diversity) of the Psychrobacter genus, provide insights into potential mechanisms of metal resistance, and exemplify the benefits of sampling remote locations for prospecting new molecular determinants. © 2018 Muñoz-Villagrán et al.